A STUDY ON LIFE SKILLS AND VALUE EDUCATION AMONG B.ED TRAINEES - J, Vijayarani; D, Geetha (International Journal of Research -GRANTHAALAYAH, 2017)
The study analyses the B.Ed trainees’ awareness & intentions of some common life skills and value education related actions. The study is based on primary data which is collected from 200 B.Ed trainees in and around Coimbatore district. The study explored the study on life skills and value education among B.Ed trainess towards teaching life skills as a way of developing practice of moral and positive social characteristic through the research. The findings reveal that there is no significant difference in the Life Skills and Value Education among B.Ed Trainees. The Trainees shall be still encouraged to give more importance to life skills and value education. The same kind of study can be carried out by increasing the number of variables and factors to get the narrowed results. The same study may be extended to another geographical region. So as to generalize the findings of the present study or compare with other regions. In the similar manner further study can be conducted to analyze Life Skills and Value Education among all subject teachers at school level as well as college level.